Ezrin Mediates Invasion and Metastasis in Tumorigenesis: A Review - Song, Yanan; Ma, Xiaokun; Zhang, Miao; Wang, Menghan; Wang, Guoyu; Ye, Ying; Xia, Wei (Frontiers in Cell and Developmental Biology, 2020)
Ezrin, as encoded by the EZR gene, is a member of the Ezrin/Radixin/Moesin (ERM) family. The ERM family includes three highly related actin filament binding proteins, Ezrin, Radixin and Moesin. These three members share similar structural properties containing an N-terminal domain named FERM, a central helical linker region, and a C-terminal domain that mediates the interaction with F-actin. Ezrin protein is highly regulated through the conformational change between a closed, inactivate form and an open, active form. As a membrane-cytoskeleton linker protein, Ezrin facilitates numerous signal transductions in tumorigenesis and mediates diverse essential functions through interactions with a variety of growth factor receptors and adhesion molecules. Emerging evidence has demonstrated that Ezrin is an oncogene protein, as high levels of Ezrin are associated with metastatic behavior in various types of cancer. The diverse functions attributed to Ezrin and the understanding of how Ezrin drives the deadly process of metastasis are complex and often controversial. Here by reviewing recent findings across a wide spectrum of cancer types we will highlight the structures, protein interactions and oncogenic roles of Ezrin as well as the emerging therapeutic agents targeting Ezrin. This review provides a comprehensive framework to guide future studies of Ezrin and other ERM proteins in basic and clinical studies.